Language and meaning: Buddhist interpretations of the "Buddha's word" in Indian and East Asian perspectives - Choe, Eun Sug (Contemporary issues in Buddhist studies, 2020)
"A comparative study on the nature of sacred language found in Indian Abhidharma texts and their counterparts by seventh-century Chinese Buddhist scholars"--